Pengaruh Kreatifitas Guru terhadap keterampilan berfikir kreatif siswa sekolah dasar - Naylah Agastiya Rinaldi; Febi Syafitri; Gusmaneli (CV. ITTC INDONESIA, 2024)
This research aims to investigate the influence of teacher creativity on students' creative thinking skills in elementary schools. Teacher creativity is considered an important factor in creating a learning environment that supports the development of students' critical and creative thinking skills. The results of the analysis show that there is a significant positive relationship between teacher creativity and students' creative thinking skills. Teachers who have an innovative and flexible teaching approach tend to encourage students to actively participate in the learning process, which in turn improves their creative thinking abilities. This research concludes that developing teacher creativity must be the main concern in efforts to improve the quality of education, especially in forming students' creative thinking skills at the elementary level.